Hybrid Meson Interpretation of the Exotic Resonance π11600 - Azzeddine Benhamida; Lahouari Semlala (Advances in High Energy Physics, 2020)
The exotic JPC=1−+resonance π11600 is examined in the framework of the Quark Model with Constituent Gluon (QMCG). We report the possibility of interpreting that resonance as qq¯g meson, with a masse ≃1.65−0.04+0.05 GeV, and a decay width to ρπ≃0.28−0.09+0.14 GeV.